Respon Pemberian Fermentasi Air Kelapa (Cocos nucifera L.) Terhadap Pertumbuhan Tanaman Selada Keriting (Lactuca sativa L. var. Grand rapids F1) - Windi Royani; Sulistyo Sidik Purnomo; Hayatul Rahmi (Jurnal Ilmiah Wahana Pendidikan, 2021)
The experiments were implemented in Lebaksari, Wadas Village, East Telukjambe Subdistrict, Karawang County from April to June 2021. The study was compiled using experimental methods with a single factor Random Group (RAK) design. The factor tested was the use of a solution of coconut water fermentation (P) yield with 5 degrees, treatment repeated 5 times. The tariff used is P0 (without treatment), P1 (25% coconut water fermentation), P2 (50% coconut water fermentation), P3 (75% coconut water fermentation), and P4 (100% coconut water fermentation). There is a real influence from the result of giving a coconut water fermentation to the high observation parameters of 7 hst and 28 hst age plants. P2 treatment (50% coconut water fermentation) shows the best result at 7 hst age plant height of 11.40 cm and the best result at 28 hst age plant height contained on treatment P1 (25% coconut water fermentation) of 31.67 cm.